Developing an Infection Prevention and Control Educational Program for Critical Care Nurses:Intervention Mapping Protocol and Social Cognitive Theory - AhmadSabbah; Rehanah Zain; Rohani Ismail; Siti Suraiya Noor; Mahaneem Mohamed; Norazliah Samsudin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim: This study aims to apply the Intervention Mapping protocol and Social Cognitive Theory in thedevelopment of an infection prevention and control education program aimed at critical care nurses.Background:Education programs have been widely used to improve awareness toward infection preventionand control, but the development of an integrated theory- and evidence-based education program tailored tocritical care nurses has not yet been discussed.Subject and Methods: Data are from the Hospital Universiti Sains Malaysia infection control records. The6-step Intervention Mapping protocol and the Social Cognitive Theory were used to develop an infectionprevention and control education material tailored to critical care nurses. The educational material was alsoinfluenced by Previous literature, hospital infection control committee, and in-charge nurses of intensivecare unit.Results: The educational material was tailored to target knowledge, self-efficacy, and risk perception thatidentified as the individual determinants of critical care nurses health behavior during assessment phase. Inaddition to physical environment and organizational support that determined as external determinants. Amatrix of change objectives was mapped out for each health behavior determinant, teaching methods, andtheir practical applications.Conclusion: Applying the Intervention Mapping protocol and the Social Cognitive Theory is effective indeveloping educational material tailored to critical care nurses to improve their self-confidence and promoteknowledge-based practice in infection prevention and control.